ANALISIS TINGKAT PEMAHAMAN MASYARAKAT KABUPATEN SERDANG BEDAGAI TERHADAP PENGGUNAAN SISTEM PEMBAYARAN NON TUNAI (Studi Kasus : PNS di Kabupaten Serdang Bedagai) - Depo Lestari Sinaga; Inggrita Gusti Sari Nasution; Irsyad Lubis (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This research aims to know the understanding level of government employee in Serdang Bedagai Region for non cash payment system utilization. The number of samples is determined by uknown populations formula and the accidental sampling technique is used to collect the samples. The object of this research is government employee of Serdang Bedagai Region who use non-cach payment system with 96 respondents.The sampling method in this field research is by giving them questionnaires. This research used descriptive data analysis technique in the form of frequency, percentage, and cross-tab. In this research, the writer used IBM SPSS Statistics 22 program.The results of this research shows that goverment employee in Serdang Bedagai Region understand the non cash payment system by using the indicator whinch consist of interpreting, exemplifying, classifying, inferring, comparing and explaining with the understanding average level at 78,75%, but utilizatoin of card payment throught of government employee are still very limited in the use of ATM cards, credit cards and debit cards.